Solution of Linear System of Equations

Download as pdf or txt
Download as pdf or txt
You are on page 1of 24

Unit 1: Linear Algebra

(Book: Advanced Engineering Mathematics by Jain and Iyengar, Chapter-3)

Topic:

Solution of Linear System of Equations

Learning Outcomes:

1. Linear System of Equations- Homogeneous and Non Homogeneous.

2. Solution of Linear System of Equations using Cramer’s rule (Determinant method).

3. Solution of Linear System of Equations using Gauss-Elimination method (Rank method).


Solution of Non-Homogeneous System of Equations:

(Cramer’s Rule)
Let us consider the following system of equations:
𝑎𝑎1 𝑥𝑥 + 𝑏𝑏1 𝑦𝑦 + 𝑐𝑐1 𝑧𝑧 = 𝑑𝑑1 (1)
𝑎𝑎2 𝑥𝑥 + 𝑏𝑏2 𝑦𝑦 + 𝑐𝑐2 𝑧𝑧 = 𝑑𝑑2 (2)
𝑎𝑎3 𝑥𝑥 + 𝑏𝑏3 𝑦𝑦 + 𝑐𝑐3 𝑧𝑧 = 𝑑𝑑3 (3)
The given system can be written as:

𝑎𝑎1 𝑏𝑏1 𝑐𝑐1 𝑥𝑥 𝑑𝑑1


𝑎𝑎2 𝑏𝑏2 𝑐𝑐2 𝑦𝑦 = 𝑑𝑑2 that is 𝐴𝐴𝐴𝐴 = 𝐵𝐵
𝑎𝑎3 𝑏𝑏3 𝑐𝑐3 𝑧𝑧 𝑑𝑑3
𝑎𝑎1 𝑏𝑏1 𝑐𝑐1 𝑥𝑥 𝑑𝑑1
Where A = 𝑎𝑎2 𝑏𝑏2 𝑐𝑐2 , X = 𝑦𝑦 , B = 𝑑𝑑2
𝑎𝑎3 𝑏𝑏3 𝑐𝑐3 𝑧𝑧 𝑑𝑑3

𝑎𝑎1 𝑏𝑏1 𝑐𝑐1 𝑑𝑑1 𝑏𝑏1 𝑐𝑐1


Let 𝐷𝐷 = 𝐴𝐴 = 𝑎𝑎2 𝑏𝑏2 𝑐𝑐2 , 𝐷𝐷𝑥𝑥 = 𝑑𝑑2 𝑏𝑏2 𝑐𝑐2 ,
𝑎𝑎3 𝑏𝑏3 𝑐𝑐3 𝑑𝑑3 𝑏𝑏3 𝑐𝑐3

𝑎𝑎1 𝑑𝑑1 𝑐𝑐1 𝑎𝑎1 𝑏𝑏1 𝑑𝑑1


𝐷𝐷𝑦𝑦 = 𝑎𝑎2 𝑑𝑑2 𝑐𝑐2 , 𝐷𝐷𝑧𝑧 = 𝑎𝑎2 𝑏𝑏2 𝑑𝑑2
𝑎𝑎3 𝑑𝑑3 𝑐𝑐3 𝑎𝑎3 𝑏𝑏3 𝑑𝑑3
Case 1. If 𝐷𝐷 ≠ 𝑂𝑂, the given system of equations is said to be consistent and
has a unique solution given by:

𝐷𝐷𝑥𝑥 𝐷𝐷𝑦𝑦 𝐷𝐷𝑧𝑧


𝑥𝑥 = , 𝑦𝑦 = , 𝑧𝑧 =
𝐷𝐷 𝐷𝐷 𝐷𝐷

Case 2. If 𝐷𝐷 = 0 and 𝐷𝐷𝑥𝑥 = 𝐷𝐷𝑦𝑦 = 𝐷𝐷𝑧𝑧 = 0 , still the given system of


equations is said to be consistent and has infinitely many solutions.

Case 3. If 𝐷𝐷 = 0 but 𝐷𝐷𝑥𝑥 , 𝐷𝐷𝑦𝑦 , 𝐷𝐷𝑧𝑧 are not all zero, then the given system of
equations is said to be inconsistent and has no solution.
Problem 1. Show that the following system of equations is consistent:
𝑥𝑥 − 𝑦𝑦 + 𝑧𝑧 = 4 (1)
2𝑥𝑥 + 𝑦𝑦 − 3𝑧𝑧 = 0 (2)
𝑥𝑥 + 𝑦𝑦 + 𝑧𝑧 = 2 (3)
Solution. The given system can be written as:

1 −1 1 𝑥𝑥 4
2 1 −3 𝑦𝑦 = 0 that is 𝐴𝐴𝐴𝐴 = 𝐵𝐵
1 1 1 𝑧𝑧 2

1 −1 1 𝑥𝑥 4
Where A = 2 1 −3 , X = 𝑦𝑦 , B = 0
1 1 1 𝑧𝑧 2
1 −1 1
Let 𝐷𝐷 = 𝐴𝐴 = 2 1 −3 = 1 1 + 3 + 1 2 + 3 + 1 2 − 1 = 10 ≠ 0.
1 1 1
As 𝐷𝐷 ≠ 0, the system of equations is consistent and has a unique solution

4 −1 1
𝐷𝐷𝑥𝑥 = 0 1 −3 = 4 1 + 3 + 1 0 + 6 + 1 0 − 2 = 20
2 1 1

1 4 1
𝐷𝐷𝑦𝑦 = 2 0 −3 = 1 0 + 6 − 4 2 + 3 + 1 4 − 0 = −10
1 2 1
1 −1 4
𝐷𝐷𝑧𝑧 = 2 1 0 = 1 2 − 0 + 1 4 − 0 + 4 2 − 1 = 10
1 1 2
𝐷𝐷𝑥𝑥 20
𝑥𝑥 = = = 2,
𝐷𝐷 10
𝐷𝐷𝑦𝑦 −10
𝑦𝑦 = = = −1,
𝐷𝐷 10
𝐷𝐷𝑧𝑧 10
𝑧𝑧 = = =1
𝐷𝐷 10
Problem 2. Show that the following system of equations is inconsistent:
4𝑥𝑥 + 9𝑦𝑦 + 3𝑧𝑧 = 6 (1)
2𝑥𝑥 + 3𝑦𝑦 + 𝑧𝑧 = 2 (2)
2𝑥𝑥 + 6𝑦𝑦 + 2𝑧𝑧 = 7 (3)
Solution. The given system can be written as:

4 9 3 𝑥𝑥 6
2 3 1 𝑦𝑦 = 2 that is 𝐴𝐴𝐴𝐴 = 𝐵𝐵
2 6 2 𝑧𝑧 7

4 9 3 𝑥𝑥 6
Where A = 2 3 1 , X = 𝑦𝑦 , B = 2
2 6 2 𝑧𝑧 7
4 9 3
Let 𝐷𝐷 = 𝐴𝐴 = 2 3 1 = 4 6 − 6 − 9 4 − 2 + 3 12 − 6 = 0.
2 6 2

6 9 3
𝐷𝐷𝑥𝑥 = 2 3 1 = 6 6 − 6 − 9 4 − 7 + 3 12 − 21 = 0
7 6 2

4 6 3
𝐷𝐷𝑦𝑦 = 2 2 1 = 4 4 − 7 − 6 4 − 2 + 3 14 − 4 = 6
2 7 2
4 9 6
𝐷𝐷𝑧𝑧 = 2 3 2 = 4 21 − 18 − 9 14 − 4 + 6 12 − 6 = −42
2 6 7
Since 𝐷𝐷 = 0 and 𝐷𝐷𝑥𝑥 = 0, 𝐷𝐷𝑦𝑦 = 6, 𝐷𝐷𝑧𝑧 = −42

So, the given system is inconsistent and has no solution.


Problem 3. Show that the following system of equations is consistent and has
infinitely many solutions:
𝑥𝑥 − 𝑦𝑦 + 3𝑧𝑧 = 3 (1)
2𝑥𝑥 + 3𝑦𝑦 + 𝑧𝑧 = 2 (2)
3𝑥𝑥 + 2𝑦𝑦 + 4𝑧𝑧 = 5 (3)
Solution. The given system can be written as:

1 −1 3 𝑥𝑥 3
2 3 1 𝑦𝑦 = 2 that is 𝐴𝐴𝐴𝐴 = 𝐵𝐵
3 2 4 𝑧𝑧 5
1 −1 3 𝑥𝑥 3
Where 𝐴𝐴 = 2 3 1 , 𝑋𝑋 = 𝑦𝑦 , 𝐵𝐵 = 2
3 2 4 𝑧𝑧 5
1 −1 3
Let 𝐷𝐷 = 𝐴𝐴 = 2 3 1 = 1 12 − 2 + 1 8 − 3 + 3 4 − 9 = 0.
3 2 4

3 −1 3
𝐷𝐷𝑥𝑥 = 2 3 1 = 3 12 − 2 + 1 8 − 5 + 3 4 − 15 = 0
5 2 4

1 3 3
𝐷𝐷𝑦𝑦 = 2 2 1 = 1 8 − 5 − 3 8 − 3 + 3 10 − 6 = 0
3 5 4
1 −1 3
𝐷𝐷𝑧𝑧 = 2 3 2 = 1 15 − 4 + 1 10 − 6 + 3 4 − 9 = 0
3 2 5
Since 𝐷𝐷 = 0 and 𝐷𝐷𝑥𝑥 = 𝐷𝐷𝑦𝑦 = 𝐷𝐷𝑧𝑧 = 0

So, the given system is consistent and has infinitely many solutions.

From equations (1) and (2):


𝑥𝑥 − 𝑦𝑦 = 3 − 3𝑧𝑧 (4)
2𝑥𝑥 + 3𝑦𝑦 = 2 − 𝑧𝑧 (5)
Solving equations (4) and (5), we get:

1
𝑥𝑥 = 11 − 10𝑧𝑧
5
1
𝑦𝑦 = 5𝑧𝑧 − 5
5
For different values of 𝑧𝑧, we get different values of x and y.

So, the system has infinitely many solutions.


Solution of Homogeneous System of Equations:

(Cramer’s Rule)
Let us consider the following system of equations:
𝑎𝑎1 𝑥𝑥 + 𝑏𝑏1 𝑦𝑦 + 𝑐𝑐1 𝑧𝑧 = 0 (1)
𝑎𝑎2 𝑥𝑥 + 𝑏𝑏2 𝑦𝑦 + 𝑐𝑐2 𝑧𝑧 = 0 (2)
𝑎𝑎3 𝑥𝑥 + 𝑏𝑏3 𝑦𝑦 + 𝑐𝑐3 𝑧𝑧 = 0 (3)
The given system can be written as:

𝑎𝑎1 𝑏𝑏1 𝑐𝑐1 𝑥𝑥 0


𝑎𝑎2 𝑏𝑏2 𝑐𝑐2 𝑦𝑦 = 0 that is 𝐴𝐴𝐴𝐴 = 0
𝑎𝑎3 𝑏𝑏3 𝑐𝑐3 𝑧𝑧 0
𝑎𝑎1 𝑏𝑏1 𝑐𝑐1 𝑥𝑥 0
Where A = 𝑎𝑎2 𝑏𝑏2 𝑐𝑐2 , X = 𝑦𝑦 , 0 = 0
𝑎𝑎3 𝑏𝑏3 𝑐𝑐3 𝑧𝑧 0

𝑎𝑎1 𝑏𝑏1 𝑐𝑐1


𝐴𝐴 = 𝑎𝑎2 𝑏𝑏2 𝑐𝑐2
𝑎𝑎3 𝑏𝑏3 𝑐𝑐3

Case 1. If 𝐴𝐴 ≠ 𝑂𝑂 (Non-singular matrix), the given system of equations has


trivial (Zero/unique) solution ( 𝑥𝑥 = 0, 𝑦𝑦 = 0, 𝑧𝑧 = 0).

Case 2. If 𝐴𝐴 = 0 (Singular matrix), the given system of equations has non-


trivial (non-Zero/infinitely many) solutions.
Problem 1. Solve the following system of homogeneous equations:
𝑥𝑥 + 2𝑦𝑦 + 3𝑧𝑧 = 0 (1)
2𝑥𝑥 + 3𝑦𝑦 − 2𝑧𝑧 = 0 (2)
4𝑥𝑥 + 7𝑦𝑦 + 4𝑧𝑧 = 0 (3)
Solution. The given system can be written as:

1 2 3 𝑥𝑥 0
2 3 −2 𝑦𝑦 = 0 that is 𝐴𝐴𝐴𝐴 = 𝑂𝑂
4 7 4 𝑧𝑧 0

1 2 3 𝑥𝑥 0
Where 𝐴𝐴 = 2 3 −2 , 𝑋𝑋 = 𝑦𝑦 , O= 0
4 7 4 𝑧𝑧 0
1 2 3
𝐴𝐴 = 2 3 −2 = 1 12 + 14 − 2 8 + 8 + 3 14 − 12 = 0.
4 7 4
So, the given system has non-trivial (infinitely many) solutions.

From equations (1) and (2):


𝑥𝑥 + 2𝑦𝑦 = −3𝑧𝑧 (4)
2𝑥𝑥 + 3𝑦𝑦 = 2𝑧𝑧 (5)

Solving these, we get 𝑥𝑥 = 13𝑧𝑧, 𝑦𝑦 = −8𝑧𝑧

For different values of 𝑧𝑧, we get different values of x and y.

So, the system has non-trivial (infinitely many) solutions.


Problem 2. Solve the following system of homogeneous equations:
𝑥𝑥 + 2𝑦𝑦 − 3𝑧𝑧 = 0 (1)
𝑥𝑥 + 𝑦𝑦 − 𝑧𝑧 = 0 (2)
𝑥𝑥 − 𝑦𝑦 + 𝑧𝑧 = 0 (3)
Solution. The given system can be written as:

1 2 −3 𝑥𝑥 0
1 1 −1 𝑦𝑦 = 0 that is 𝐴𝐴𝐴𝐴 = 𝑂𝑂
1 −1 1 𝑧𝑧 0

1 2 −3 𝑥𝑥 0
Where 𝐴𝐴 = 1 1 −1 , 𝑋𝑋 = 𝑦𝑦 , O= 0
1 −1 1 𝑧𝑧 0
1 2 −3
𝐴𝐴 = 1 1 −1 = 1 1 − 1 − 2 1 + 1 − 3 −1 − 1 = 2 ≠ 0.
1 −1 1
So, the given system has trivial (zero) solution that is
𝑥𝑥 = 0, 𝑦𝑦 = 0, 𝑧𝑧 = 0.
Problem 3. Determine the values of 𝑘𝑘 for which the system of equations:
𝑥𝑥 − 𝑘𝑘𝑘𝑘 + 𝑧𝑧 = 0 (1)
𝑘𝑘𝑥𝑥 + 3𝑦𝑦 − 𝑘𝑘𝑘𝑘 = 0 (2)
3𝑥𝑥 + 𝑦𝑦 − 𝑧𝑧 = 0 (3)
has (I) Only trivial solution (II) Non-trivial solution
Solution. The given system can be written as:

1 −𝑘𝑘 1 𝑥𝑥 0
𝑘𝑘 3 −𝑘𝑘 𝑦𝑦 = 0 that is 𝐴𝐴𝐴𝐴 = 𝑂𝑂
3 1 −1 𝑧𝑧 0
1 −𝑘𝑘 1 𝑥𝑥 0
Where 𝐴𝐴 = 𝑘𝑘 3 −𝑘𝑘 , 𝑋𝑋 = 𝑦𝑦 , O= 0
3 1 −1 𝑧𝑧 0
1 −𝑘𝑘 1
𝐴𝐴 = 𝑘𝑘 3 −𝑘𝑘 = 1 −3 + 𝑘𝑘 + 𝑘𝑘 −𝑘𝑘 + 3𝑘𝑘 + 1 𝑘𝑘 − 9 .
3 1 −1
𝐴𝐴 = 2𝑘𝑘 2 + 2𝑘𝑘 − 12

(I) For trivial solution: 𝐴𝐴 ≠ 0

⟹ 2𝑘𝑘 2 + 2𝑘𝑘 − 12 ≠ 0 ⟹ 𝑘𝑘 ≠ 2 𝑎𝑎𝑎𝑎𝑎𝑎 𝑘𝑘 ≠ −3

(II) For non-trivial solution: 𝐴𝐴 = 0

⟹ 2𝑘𝑘 2 + 2𝑘𝑘 − 12 = 0 ⟹ 𝑘𝑘 = 2 𝑜𝑜𝑜𝑜 𝑘𝑘 = −3

You might also like